2014
DOI: 10.1007/s11356-014-2929-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peat fires on the characteristics of humic acid extracted from peat soil in Central Kalimantan, Indonesia

Abstract: When peat forest fires happen, it leads to burn soil and also humic acids as a dominant organic matter contained in peat soil as well as the forest. The structure and properties of humic acids vary depending on their origin and environment, therefore the transformation of humic acid is also diverse. The impacts of the peat fires on peat soil from Central Kalimantan, Indonesia were investigated through the characterization of humic acids, extracted from soil in burnt and unburnt sites. The characterization of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Other researches have demonstrated lower N content in the top soil in the burnt sites after recent fires (Milner, 2013;Saharjo & Nurhayati, 2005) likely due to the volatilization of N during peat combustion and biomass removal and additions of low-lability N to the peat from fresh litter of non-peatland species (Könönen et al, 2015). Others studies have shown significant increases in soil total N (Andriesse, 1988;Yustiawati et al, 2015), probably due to the presence of ashes. Some others indicated short-term increases in soil N content followed by a longer-term decline (Wan, Hui, & Luo, 2001), likely due to N loss by denitrification or leaching (Knicker, 2007).…”
Section: Radiocarbon Datamentioning
confidence: 92%
“…Other researches have demonstrated lower N content in the top soil in the burnt sites after recent fires (Milner, 2013;Saharjo & Nurhayati, 2005) likely due to the volatilization of N during peat combustion and biomass removal and additions of low-lability N to the peat from fresh litter of non-peatland species (Könönen et al, 2015). Others studies have shown significant increases in soil total N (Andriesse, 1988;Yustiawati et al, 2015), probably due to the presence of ashes. Some others indicated short-term increases in soil N content followed by a longer-term decline (Wan, Hui, & Luo, 2001), likely due to N loss by denitrification or leaching (Knicker, 2007).…”
Section: Radiocarbon Datamentioning
confidence: 92%
“…[Parker et al, 2016] In addition to heating temperature, the burning process is also affected by the history of previous burning. For instance, TG-DTA analysis of humic acid extracted from peat sampled at a burned area in Kalimantan does not have a significant peak corresponding to the temperature of charcoal formation, while it still has a strong signal in the temperature range of charcoal burning [Yustiawati et al, 2015]. On the other hand, humic acid from unburned peat demonstrated peaks for both charcoal formation and burning upon TG-DTA analysis.…”
mentioning
confidence: 99%
“…For instance, González-Pérez et al (2004) report that burning events caused carbon loss by over 50% in Humic Cambisol (Inceptsol) up to a depth of 0.10 m, and carbon loss was also detected in North American soils subjected to burning practices for 10 years. Moreover, Yustiawati et al (2014) found that the H/C ratio in HA from burned soil is lower than in HA from unburned soil. Despite these findings, the effects reported in other studies were not detected in the present investigation.…”
Section: Elemental Composition Of Humic Acidsmentioning
confidence: 98%